A selective inhibition of c-Fos/activator protein-1 as a potential therapeutic target for intervertebral disc degeneration and associated pain. Issue 1 (December 2017) - Makino, Hiroto; Seki, Shoji; Yahara, Yasuhito; Shiozawa, Shunichi; Aikawa, Yukihiko; Motomura, Hiraku; Nogami, Makiko; Watanabe, Kenta; Sainoh, Takeshi; Ito, Hisakatsu; Tsumaki, Noriyuki; Kawaguchi, Yoshiharu; et al.
Abstract Intervertebral disc (IVD) degeneration is a major cause of low back pain. The transcription factor c-Fos/Activator Protein-1 (AP-1) controls the expression of inflammatory cytokines and matrix metalloproteinases (MMPs) that contribute to the pathogenesis IVD degeneration. We investigated the effects of inhibition of c-Fos/AP-1 on IVD degeneration and associated pain. A selective inhibitor, T-5224, significantly suppressed the interleukin-1β-induced up-regulation ofMmp-3, Mmp-13 andAdamts-5 transcription in human nucleus pulposus cells and in a mouse explant culture model of IVD degeneration. We used a tail disc percutaneous needle puncture method to further assess the effects of oral administration of T-5224 on IVD degeneration. Analysis of disc height, T2-magnetic resonance imaging (MRI) findings, and histology revealed that IVD degeneration was significantly mitigated by T-5224. Further, oral administration of T-5224 ameliorated pain as indicated by the extended tail-flick latency in response to heat stimulation of rats with needle-puncture-induced IVD degeneration. These findings suggest that the inhibition of c-Fos/AP-1 prevents disc degeneration and its associated pain and that T-5224 may serve as a drug for the prevention of IVD degeneration.